Women and training : a critical analysis : a thesis in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Battleday, Suzanne (Massey University, 1998)
From the point of view of its implications for women, this thesis critically investigates the official discourse of training in New Zealand in the late 1980s and 1990s, and explores its effects within the Polytechnic sector. The more theoretical side of the project involves discussing the changing meanings of 'training' and its entangled relationship with 'education'. I then conduct a thorough examination of the key statement of the new training discourse - Education for the Twenty-first Century - and give a twofold account of its structure and meaning. One part of this discourse is oriented towards social pluralism and equity, but this strand is undercut by the dominant 'human capital' perspective which ultimately holds little prospect for real advance in women's training and labour market situation. The more empirical dimension of the thesis involves a quantitative analysis of enrolment statistics, a discourse analysis of Polytechnic reports, and a questionnaire/interview schedule with senior staff within one Polytechnic. Overall, there is little evidence that government strategy and ideology are contested within Polytechnics, and whilst women's participation rates may be buoyant, the content of their training courses and the consequent image of what sort of life women make for themselves could be seen as surprisingly traditional. At all levels of the work, I try to highlight important indications of progress or contradiction, where they exist. But on the whole, the sobering thought emerging from the thesis is that there is still a long way to go for a properly non-sexist training agenda.
Keywords: New Zealand; Occupational training for women; Women -- Vocational education; Technical education; Education -- Aims and objectives; Sex discrimination in education